Impact of career development, compensation, work-life balance and psychological well-being on employee retention in hospitality industry in Malaysia - Nawaz, Allah (2019)
In Malaysia, the hospitality industry has experienced a positive growth with the development of worldwide hospitality industry in current years. The hospitality industry considered as the major pillars of national economy. As the hospitality industry is the service-oriented business and talented human resource is considered very important in the hospitality industry. Since the hospitality industry is one of those industries that are experience issues regarding employee retention. This study is conducted in the four- and five-star hotel in the tourist places in Penang and Langkawi, Malaysia. The basic aim of research is to examine to the factors that can influence the employee retention. Four factors namely career development, compensation, work-life balance and psychological well-being have been recognized that can highly impact the employee retention. For this purpose, questionnaires were circulated by self-administered and overall response were 164 employees. Gather data were analysis into database by using Statistical Package for Social Science (SPSS) software version 25. The findings of the survey were analyzed, produced and summarized into statistical analysis which comprise of description analysis, correlation analysis and regression analysis. The outcomes showed that career development, compensation, work-life balance and psychological well-being has significant relationship with employee retention. Therefore, it is vital hotel companies to develop and applied they’re by offering career progression, handsome compensation packages, better work-life balance and mental happiness to retain the talented employees.